PENDEKATAN STUDI MAKRO DALAM PERENCANAAN WILAYAH - WIDHIANTINI - (SOCA: Jurnal Sosial Ekonomi Pertanian, 2008)
The goal of this macro study is preparing an integrated development planning for aregency. The specific goals are to identify and analyze potential, problem, and need in theregency; and to recommend programs needed by the people to make a sustainabledevelopment comes true.Macro study approach is a scientific method combining rational method based on thereview of previous studies by government agencies with empirical method using surveytechnique. Data collected include primary and secondary. Secondary data an gained frommany institutions, and primary data are collected using observation and interview methods.Bali area has no natural resources like forest, mining, petroleum and coal that giveincome for the region or government. Therefore, the review of this macro study is veryrelevant in developing a region, especially rural area based on its strengths, exampleKarangasem Regency.The reason to choose Karangasem Regency are as follows (1) Karangasem Regency isan area of agricultural commodity and (2) based on the Act No.24/1992, KarangasemRegency is located in quadrant III, i.e., rural corporate area supported by tourism area.The result of study indicated that: (1) potentials of this regency are: (a) laboreradsorbed in agricultural sector is 75,62%, (b) high productive age is 70%, (c) highentrepreneurship of villagers, (d) more than 50% of women are working in small industry, (e)the existence of written and oral regulation from subak and customary village institution, and(f) life principle which is still attached on Balinese (Tri Hita Karana). Problem of this regencyare: (a) high input price, (b) limited of land, capital, marketing, and technology, (c)unpredictable price fluctuation and season of agricultural products, (d) low access to continuehigh school and courses due to limited facility, (e) low treatment skill of volunteer, and (f)limited local government finance. The needs of this regency are: (a) guarantee of agriculturalproduct price, (b) market that can collect all production yield, (c) support and capitalassistance from government or private to expand UKM, (d) skill training and capitalassistance from local government for small industry, (e) finance assistance from foreigner forregional development, and (f) multi way and coordination among the local people (customvillage) and government coordinators.